Didactic training model of the general surgeon for the care of patients with colon cancer - Zenén Rodríguez Fernández; Arlines Wilson Mustelier; Erick Manuel Milán Dinza; Benjamín Deulofeu Betancourt (Edumecentro, 2023)
Background: currently epistemological and praxiological restrictions are observed in the training of the General Surgery resident. The hermeneutic-dialectical logic of such training is expressed in its relationship with contextual surgical practice; the development of surgical skills proceeds through the in-service training. Objective: to design a didactic model of surgical-care training in the in-service training of the General Surgery resident, for the comprehensive care of patients with colon cancer. Methods: a development investigation was carried out in the "Saturnino Lora" and "Juan B. Zayas" hospitals in Santiago de Cuba during 2021. Theoretical methods were used: analysis-synthesis, systematization and generalization of experiences, holistic-dialectical, modeling and hermeneutic approach; empirical ones: survey and interview with residents, specialists and experts from both hospitals. Results: the designed model is based on the systematization and generalization of the authors' experiences concerning the preoperative, operative, and postoperative periods of surgery for this neoplasm. Conclusions: the didactic model was validated by experts as pertinent, feasible and applicable; Its contradiction is the relationship between the algorithmic sequential logic of surgical practice and the hermeneutic-dialectical logic of the training process of the resident in General Surgery, in order to help reduce the insufficiencies and limitations of this professional during the training process.